Na ponta da lança: uma análise contextualizada da atividade de policiamento ostensivo capixaba na última década - Figueiredo, Sabrina Oliveira de (2023)
Military police organizations are constant targets of political, social, media and academic debates and reflections. Despite the organization being the focus of discussions under different lenses, ostensible policing, which is the manifestation of military police work, is a subject that is little considered in research and academic productions, either due to the difficulty of access to the field by external researchers, due to the sensitivity of nature of the police organization or other reasons. In this study, we sought to analyze the activity of ostensive policing from changes in the context of work of the military police in Espírito Santo, in the last decade (2010-2020). Work is considered, in this study, from the ergological theoretical-analytical approach, which understands it as a human activity that contemplates the object (physical materials, technical knowledge and procedures that guide its execution), the worker (physical aspects, historical and social) and the variability of the environment (physical, social and others, which lead to the adaptations produced by the worker). The methodological approach adopted was the Grounded Theory, in the Constructivist perspective, which favored the co-construction of the research data through different perspectives on the studied phenomenon, including the participating police officers and the researcher with the participants and the research context. The empirical material of the research brings together the content of interviews carried out with 40 military police officers from different levels of activity, direct observation of work activity, existing texts and memos. The study showed that changes in the context of police work were manifested in the governmental, organizational and social spheres. Thus, the substantive theory derived from the study predicts, in summary, that (i) political interference in the military police organization influence the (un)availability of investments, the lack of (re)composition of police personnel and the inadequacy of wage readjustments for the category (governmental scope); (ii) the organization directs its attention to the physical elements of the policing activity, such as the acquisition of equipment aimed at its achievement, but fails to privilege the human elements by not paying attention to the consequences of the 2017 strike for socio-professional relations and the presence and influence of a new police profile (organizational scope); and (iii) the variability of the social environment generate implications and, at the same time, are influenced by the renormalization of policing, which, consequently, have produced individualized community patrolling and ordinary repressive patrolling (social scope).